Pre-professional internships in the development of skills and employability of accounting students: a case study from a Peruvian University - Carranza Guevara, Rosas; Cruz Caro, Omer; Tarrillo Perez, Doris; Reina Marín, Yuri; Portocarrero Ramos, Heily Consepción; Contreras Portocarrero, Juana del Pilar; Sánchez Bardales, Einstein; Campos Trigoso, Jonathan Alberto; Chávez Santos, River (Frontiers in Education, 2025)
Pre-professional internships are an essential mechanism for consolidating academic training and facilitating students’ transition into the labor market. The objective of this study was to evaluate pre-professional internships in the development of professional skills and the perception of employability among accounting students. A cross-sectional, non-experimental quantitative design was used. The study employed a structured questionnaire composed of seven dimensions, complemented with open-ended questions whose responses were examined through basic descriptive content exploration. The sample consisted of 60 participants, including interns and graduates entering the labor market. The results show that more than 70% of respondents value internships as a key space for strengthening accounting competencies, soft skills, and integration into organizational environments. It was also evident that internships increase perceptions of employability and academic motivation, although limitations persist in access to technological resources, academic planning, and innovative teaching methodologies. The comparative analysis did not reveal statistically significant differences between classes, although gaps were identified in the perceived preparation to face professional challenges. It is concluded that pre-professional internships represent a determining factor in building professional identity and strengthening sustainable employability, underscoring the need for curriculum redesign, stronger academic support, and greater collaboration with industry.